Design and Construction of A Vortex Type Turbine Driving A 100 Watt Generator - Jose Mikael Saragih; Tambos A. Sianturi; Azarya Siahaan (International journal of technology and education research, 2026)
This study aims to describe the design and construction of a vortex-type turbine driving a 100-watt generator. The research method used is an experimental method, namely by designing, making, and testing a vortex turbine to determine the system's ability to produce 100 watts of electrical power. Based on the test results, turbines with blade angle variations of 30°, 45° and 60° at the same water discharge of 2,026L/s, it was found that the 60° blade angle produced better performance. This is shown at an angle of 60° obtaining a turbine speed of 714.882 and a hydrostatic pressure of 121,590 Pa, which is higher than an angle of 30° which obtains a turbine speed of 563.786 and a hydrostatic pressure of 121,590 and an angle of 45° which only obtains a turbine speed of 740.1 and a hydrostatic pressure of 95,245. Thus, it can be concluded that the blade angle affects turbine performance, where the 60° angle in this test is able to optimize the conversion of water energy into mechanical and electrical energy more effectively than the 30° and 45°